2023
DOI: 10.1039/d3bm00873h
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic hyaluronic acid coating preserves the phenotypes of lymphatic endothelial cells

Sanjoy Saha,
Fei Fan,
Laura Alderfer
et al.

Abstract: Lymphatic endothelial cells (LECs) play a critical role in the formation and maintenance of the lymphatic vasculature, which is essential for the immune system, fluid balance, and tissue repair. However,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…We demonstrate that these dynamic hydrogels can provide spatially controlled substrates for the culture of human LECs to direct lymphatic CLS formation. The presentation of HA to the surface of LECs has been shown to preserve the lymphatic phenotypes . Modulating the viscoelastic properties of the HA hydrogels can further promote lymphatic CLS formation by enhanced expression of key lymphatic markers, such as LYVE-1 , podoplanin , and Prox1 , along with expression of Nrp2 , VEGFR2 , and VEGFR3 to enhance VEGF-C stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrate that these dynamic hydrogels can provide spatially controlled substrates for the culture of human LECs to direct lymphatic CLS formation. The presentation of HA to the surface of LECs has been shown to preserve the lymphatic phenotypes . Modulating the viscoelastic properties of the HA hydrogels can further promote lymphatic CLS formation by enhanced expression of key lymphatic markers, such as LYVE-1 , podoplanin , and Prox1 , along with expression of Nrp2 , VEGFR2 , and VEGFR3 to enhance VEGF-C stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The presentation of HA to the surface of LECs has been shown to preserve the lymphatic phenotypes. 71 Modulating the viscoelastic properties of the HA hydrogels can further promote lymphatic CLS formation by enhanced expression of key lymphatic markers, such as LYVE-1, podoplanin, and Prox1, along with expression of Nrp2, VEGFR2, and VEGFR3 to enhance VEGF-C stimulation. Whereas previous studies have shown the importance of matrix stiffness for lymphatic tube formation, 46,54 this report offers evidence supporting a role for matrix viscoelasticity in promoting lymphatic development and lymphatic CLS formation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the lymphatic system aids in fluid drainage, removing immune complexes and interstitial matrix components that break down during regular body balance and tissue damage. 1…”
Section: Introductionmentioning
confidence: 99%